Recent advances in copper sulfide nanoparticles for cancer diagnosis and therapy - Guangyao Li; Xiang Li; Zhangrong Lou; Junnan Xu; Yiwen Ma; Xiaorui Li; Qiang Liu; Tao Sun (Materials Today Bio)
Cancer, a highly heterogeneous and complex disease characterized by multiple genetic and metabolic abnormalities, remains one of the leading causes of death worldwide. Although conventional treatments such as surgery, chemotherapy, and radiotherapy, can mitigate the disease to some extent, their efficacy remains constrained by various factors. In recent years, nanotechnology has emerged as a promising approach for cancer treatment, with copper-based nanomaterials garnering significant attention due to their unique physicochemical properties and favorable biocompatibility. Copper sulfide (CuS) nanomaterials, in particular, have shown great potential as a versatile platform for both diagnosis and therapy, primarily due to their superior photothermal properties. Moreover, copper plays a crucial role in tumorigenesis, progression, and multiple cell death pathways, further highlighting its potential in cancer therapy. This review discusses the metabolic regulation of copper and its diverse roles in tumor biology, examines the applications and recent advances of CuS nanomaterials in cancer therapy, and explores their future potential in cancer diagnosis and treatment.